2020
DOI: 10.3892/mmr.2020.10982
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from adipose‑derived stem cells promote chondrogenesis and suppress inflammation by upregulating miR‑145 and miR‑221

Abstract: osteoarthritis (oa) is one of the most prevalent joint disorders globally. Patients suffering from oa are often obese and adiposity is linked to chronic inflammation. In the present study, the potential of using exosomes isolated from adipose-derived stem cells (adScs) as a therapeutic tool for reducing chronic inflammation and promoting chondrogenesis was investigated using patient-derived primary cells. First, it was tested whether patient-derived adScs could differentiate into chondrogenic and osteogenic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 23 publications
0
68
0
Order By: Relevance
“…209 • Promote chondrocytes viability, maintain the balance of anabolism and catabolism via miR-100-5p-mediated mTOR inhibition and autophagy enhancement. 146 • Enhance proliferation and chondrogenic potential of periosteal cells via upregulating miR-145 and miR-221 211 • Down-regulate mitochondrial membrane potential. 208 • promote chondrogenesis in periosteal cells and increase chondrogenic markers 211 • Show the potential anti-inflammatory and chondro-protective effects.…”
Section: Ultracentrifugation and Ultrafiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…209 • Promote chondrocytes viability, maintain the balance of anabolism and catabolism via miR-100-5p-mediated mTOR inhibition and autophagy enhancement. 146 • Enhance proliferation and chondrogenic potential of periosteal cells via upregulating miR-145 and miR-221 211 • Down-regulate mitochondrial membrane potential. 208 • promote chondrogenesis in periosteal cells and increase chondrogenic markers 211 • Show the potential anti-inflammatory and chondro-protective effects.…”
Section: Ultracentrifugation and Ultrafiltrationmentioning
confidence: 99%
“…146 • Enhance proliferation and chondrogenic potential of periosteal cells via upregulating miR-145 and miR-221 211 • Down-regulate mitochondrial membrane potential. 208 • promote chondrogenesis in periosteal cells and increase chondrogenic markers 211 • Show the potential anti-inflammatory and chondro-protective effects. 208,209 • Ameliorate the pathological severity of articular cartilage and partially improve the abnormal gait.…”
Section: Ultracentrifugation and Ultrafiltrationmentioning
confidence: 99%
“…Furthermore, in the next study, they confirmed that microvesicles and exosomes secreted from ASCs could affect the metabolism of OA chondrocytes by modulating inflammatory and degradative pathways associated with joint destruction (Tofiño-Vian et al, 2018). Zhao et al (2020) separated the patient ASC-exos, which exerted a strong stimulatory effect on chondrocyte migration and proliferation with the upregulation of miR-145 and miR-221 in the model of the inflammation-inflicted oxidative stress. Woo et al also confirmed that human ASC-EVs could potentially protect cartilage from degeneration and could delay cartilage degeneration in OA rat and mouse models.…”
Section: Asc-exos In Bone Tissue Damagementioning
confidence: 54%
“…These changes were likely due to reduced activity of NF-kB and AP-1. Similarly, Zhao et al (2020) reported that AT-MSC-derived exosomes displayed chondroprotective and anti-inflammatory properties. They found that co-culture of AT-MSC-derived exosomes with activated synovial fibroblasts reduced the expression of IL-6 and TNF-α, whereas the expression of IL-10 was enhanced.…”
Section: Therapeutic Effects Of Mscs In Oamentioning
confidence: 88%
“…Co-culture with chondrocytes protected from H 2 O 2 -induced apoptosis. Interestingly, treatment with exosomes stimulated chondrogenesis and increased the expression of chondrogenic markers, such as collagen type II and β-catenin (Zhao et al, 2020). More recently, it was evidenced that human AT-MSC-derived EVs increased human OA chondrocyte proliferation and migration, enhanced type II collagen synthesis, and reduced IL-1-mediated expression of key catabolic enzymes, MMP-1, MMP-3, MMP-13, and ADAMTS-5 (Woo et al, 2020).…”
Section: Therapeutic Effects Of Mscs In Oamentioning
confidence: 99%